D.N. Jha. ANCIENT INDIA IN HISTORICAL OUTLINE. 3rd EDITION - Matthew Gray Marsh (Journal of Ancient History and Archaeology)
D.N. Jha. Ancient India in Historical Outline. 3rd Ed. New Delhi, IN: Manohar Publishers & Distributors, 2015, 238p., ISBN 978-93-5098-075-0